Relevansi Pencatatan Nikah Sirri dalam Kartu Keluarga Menurut Hak Asasi Manusia dan Maqashid Syariah - Ifrohati; Sintri (Journal of Sharia and Legal Science, 2023)
One of the requirements for registering a marriage is to make a family card. Therefore, registration of marriage is very important for married couples. However, it turns out that sirri marriages can also have a family card, even though this marriage is not a legal marriage according to state law. Thus, this study aims to examine the registration of sirri marriages in family cards both in terms of human rights and maqashid sharia. The type of research used is qualitative research (libraries or library research), namely with a normative approach. The results of the study found that the relevance of Siri Marriage Registration in the Family Card to Human Rights is with regard to citizenship status rights or children's civil rights such as birth certificates. Apart from that, it is a form of legal protection for children, such as those related to living expenses and living costs, as well as mutual inheritance rights inherited from their parents. As for the Relevance of Siri Marriage Registration in the Family Card from the perspective of Maqāṣid asy-Syarīʿah, it is a primary need (adl-dlarūriyāt) especially for children related to hifdzu an-nasl (safeguarding offspring).